SHARIAH RISK FACTOR AND STOCK RETURN IN THE INDONESIAN STOCK MARKET DURING COVID-19 AND THE RUSSIA-UKRAINE CONFLICT - Dharani, Munusamy; Hassan, M. Kabir; Hermawan, Danny (Journal of Islamic Monetary Economics and Finance, 2024)
Using a sample of 544 Indonesian stocks, we examine the performance of the Shariah and non-Shariah stocks from 2018-2023. Employing panel regressions to investigate the impact of the Shariah investment principles on the average stock returns, we observe a positive relationship between the Shariah firms and average stock return in the market. Consequently, the study forms the Shariah and non-Shairah portfolios and analyzes their performance using the asset pricing model. We document evidence that the Shariah portfolio provides a higher abnormal return than the non-Shariah portfolio. Further, we report that the Shariah portfolio provides a higher abnormal return than the non-Shariah portfolio after controlling COVID-19 and the Russia-Ukraine war. Finally, we create the Shariah risk factor and conclude that it is one factor that explains the deviation in the stock return in the Indonesian stock market. The study recommends that policymakers consider this factor to derive the cost of equity, discount rate, and cost of capital.